2004
DOI: 10.2527/2004.82102964x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of additional starch or fat in late-gestating high nonstarch polysaccharide diets on litter performance and glucose tolerance in sows1,2

Abstract: The effects of feeding additional starch or fat from d 85 of gestation until parturition on litter performance and on glucose tolerance in sows that were fed a diet with a high level of fermentable nonstarch polysaccharides (NSP) were studied. The day after breeding, 141 multiparous sows were assigned to the experiment. At d 85 of gestation, sows were assigned to the treatments. Sows were fed 3.4 kg/d (as-fed basis) of a high-NSP diet or the same quantity of the high-NSP diet and an additional 360 g of starch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
1
10
0
2
Order By: Relevance
“…The transition from gestation to lactation is characterized by physiological and metabolic changes, such as a progressive decrease in insulin sensitivity during late gestation and lactation (Pere et al, 2000;Pere and Etienne, 2007). During lactation, insulin resistance is negatively correlated with the feed intake of sows (Van der Peet-Schwering et al, 2004;Mosnier et al, 2010). Several studies have shown that soluble dietary fiber can improve insulin sensitivity in mice or rats (Song et al, 2000;Isken et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The transition from gestation to lactation is characterized by physiological and metabolic changes, such as a progressive decrease in insulin sensitivity during late gestation and lactation (Pere et al, 2000;Pere and Etienne, 2007). During lactation, insulin resistance is negatively correlated with the feed intake of sows (Van der Peet-Schwering et al, 2004;Mosnier et al, 2010). Several studies have shown that soluble dietary fiber can improve insulin sensitivity in mice or rats (Song et al, 2000;Isken et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Foram utilizados 14 artigos distribuídos nos continentes europeu e americano, publicados de 2000 a 2006 em revistas indexadas internacionais (PRUNIER et al, 2001, SINCLAIR et al, 2001COOPER et al, 2001a, CLOWES et al, 2003MAES et al, 2004;RAMANAU et al, 2004;VAN DER PEET-SCHWERING et al, 2004;YOUNG et al, 2004;RENSIS et al, 2005;YOUNG et al, 2005b;LANDBLOM et al, 2006) e nacionais (GUEDES & NOGUEIRA, 2000;HASHIMOTO et al, 2004;LIMA et al, 2006). As informações relevantes das seções de material e métodos e resultados de cada artigo foram inseridas numa base de dados elaborada em planilha Excel.…”
Section: Methodsunclassified
“…For many years, research focused on the beneficial effects of additional fat in late gestation on piglet birth weight, but the specific fatty acid profile of the supplemented fat source was not taken into account (Seerley et al., 1981; Cieslak et al., 1983; Averette et al., 1999; van der Peet‐Schwering et al., 2004). More recently, studies on the supplementation of specific fatty acids such as eicosapentaenoic acid (EPA, C20:5 n‐3) and docosahexaenoic acid (DHA, C22:6 n‐3), have been performed.…”
Section: Introductionmentioning
confidence: 99%